2021
DOI: 10.1038/s41591-021-01410-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination on new SARS-CoV-2 infections in the United Kingdom

Abstract: The effectiveness of COVID-19 vaccination in preventing new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in the general community is still unclear. Here, we used the Office for National Statistics COVID-19 Infection Survey—a large community-based survey of individuals living in randomly selected private households across the United Kingdom—to assess the effectiveness of the BNT162b2 (Pfizer–BioNTech) and ChAdOx1 nCoV-19 (Oxford–AstraZeneca; ChAdOx1) vaccines against any new SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
268
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(297 citation statements)
references
References 23 publications
13
268
1
Order By: Relevance
“…3), where pooled estimate indicates vaccine effectiveness of 91% (95% confidence interval 81%-95%). The findings from the meta-analysis of three studies (Chung et al 2021;Lopez Bernal et al 2021;Pritchard et al 2021) which presented effect measure as OR are also consistent (pooled OR = 0.19; 95% confidence interval 0.09-0.40) and show vaccine effectiveness of 81% (95% confidence interval 60%-91%) 7 days or more after the second dose of BNT162b2 mRNA vaccine. The meta-analysis of three studies (Hall et al 2021;Regev-Yochay et al 2021;Thompson et al 2021) which presented effect measure as HR reported pooled HR of 0.12 (95% confidence interval: 0.08-0.16; Fig.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…3), where pooled estimate indicates vaccine effectiveness of 91% (95% confidence interval 81%-95%). The findings from the meta-analysis of three studies (Chung et al 2021;Lopez Bernal et al 2021;Pritchard et al 2021) which presented effect measure as OR are also consistent (pooled OR = 0.19; 95% confidence interval 0.09-0.40) and show vaccine effectiveness of 81% (95% confidence interval 60%-91%) 7 days or more after the second dose of BNT162b2 mRNA vaccine. The meta-analysis of three studies (Hall et al 2021;Regev-Yochay et al 2021;Thompson et al 2021) which presented effect measure as HR reported pooled HR of 0.12 (95% confidence interval: 0.08-0.16; Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Of these, 19 studies were excluded since they either did not report vaccine effectiveness, reported non-specific outcomes such as COVID-19-related mortality and COVID-19-related hospitalization, or reported unadjusted effectiveness estimates. Therefore, 19 studies (Angel et al 2021;Björk et al 2021;Cabezas et al 2021;Chung et al 2021;Dagan et al 2021;Emborg et al 2021;Fabiani et al 2021;Glampson et al 2021;Gras-Valentí et al 2021;Haas et al 2021;Hall et al 2021;Lopez Bernal et al 2021;Mason et al 2021;Monge et al 2021;Pritchard et al 2021;Regev-Yochay et al 2021;Shrotri et al 2021;Swift et al 2021;Thompson et al 2021) were included for this meta-analysis; 12 studies (Chung et al 2021;Dagan et al 2021;Emborg et al 2021;Fabiani et al 2021;Glampson et al 2021;Gras-Valentí et al 2021;Haas et al 2021;Lopez Bernal et al 2021;Mason et al 2021;Monge et al 2021;Regev-Yochay et al 2021) were retrospective in design with seven database reviews (Dagan et al 2021;Emborg et al 2021;Glampson et al 2021;Haas et al 2021;Mason et al 2021;Monge et al 2021;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, vaccine efficacy against clinical outcomes as well as antibody responses should contribute to prioritization decisions. In a related UK-wide study 22 and a study from Israel 23 , high levels of protection from infection following natural infection were observed that were comparable to those seen after two doses of vaccination without prior infection. In the latter study 23 , the authors question whether previously infected individuals require vaccination; our data show that vaccination does boost antibody responses after previous infection, although the impact on protection from infection over varying timescales requires further study.…”
Section: Discussionmentioning
confidence: 80%
“…ChAdOx1 nCoV-19 has been fully approved in Brazil and approved for emergency use in 64 additional countries. The effectiveness of the vaccine is 92% and is 79% against symptomatic infection 18,19 .…”
Section: Auro Vaccines Llc and The Coalition Of Epidemic Preparedness Innovations (Cepi)mentioning
confidence: 99%